2021
DOI: 10.1063/5.0035650
|View full text |Cite
|
Sign up to set email alerts
|

Impact of area scaling on the ferroelectric properties of back-end of line compatible Hf0.5Zr0.5O2 and Si:HfO2-based MFM capacitors

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…At higher temperatures, a reduced field cycling endurance (e.g. of at least one decade at 75°C [11]) can be hindered by material improvements such as replacing HSO for Hf0.5Zr0.5O2 as in [12]. Overall, capacitor area scaling down to the target capacitor size is expected to be non-detrimental to electric field cycling reliability.…”
Section: Wake-up and Field Cycling Endurancementioning
confidence: 99%
“…At higher temperatures, a reduced field cycling endurance (e.g. of at least one decade at 75°C [11]) can be hindered by material improvements such as replacing HSO for Hf0.5Zr0.5O2 as in [12]. Overall, capacitor area scaling down to the target capacitor size is expected to be non-detrimental to electric field cycling reliability.…”
Section: Wake-up and Field Cycling Endurancementioning
confidence: 99%
“…These measures enable a reduced thermal budget to crystallize the HZO, necessary for the successful integration of ferroelectric HZO on InAs. However, despite these measures, the endurance of InAs/HZO ferroelectric capacitors is at this point much lower than its MIM counterparts (10 8 –10 10 cycles), [ 44 ,‐ 46 ] highlighting the necessity to minimize the thermal budget for HZO integration onto the thermally sensitive III–V semiconductors. Although device scaling down to sub‐micron‐sized devices has proved to significantly improve the endurance properties, [ 46 ] our results here indicate that research into ns‐annealing [ 37 ] or annealing‐free approaches [ 47 ] may be necessary to truly enable high‐performance III–V‐based ferroelectric devices.…”
Section: Discussionmentioning
confidence: 99%
“…9,12 It has been reported that the cycle-tobreakdown of FE-HfO 2 capacitors is further improved by a factor of 10 2 to 10 4 by reducing the capacitor area by 4 orders of magnitude. 41,42 This is because dielectric breakdown is caused by the formation of a conduction path, which has a lower probability of occurring in a smaller area. 43 Therefore, the cycle-to-breakdown of 10 12 cycles at 200 kHz or 10 14 cycles at 20 MHz found in this study can be considered a lower limit of cycle-to-breakdown in smaller capacitors.…”
Section: Low Operating Voltagementioning
confidence: 99%